A Case of Blastic Plasmacytoid Dendritic Cell Neoplasm Extensively Studied by Flow Cytometry and Immunohistochemistry. (20th March 2017) - Pennisi, Martina; Cesana, Clara; Cittone, Micol Giulia; Bandiera, Laura; Scarpati, Barbara; Mancini, Valentina; Soriani, Silvia; Veronese, Silvio; Truini, Mauro; Rossini, Silvano; Cairoli, Roberto
Abstract : Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare hematologic malignancy with aggressive clinical course and poor prognosis. Diagnosis is based on detection of CD4 + CD56 +, C D 123 h i g h, TCL-1 +, and blood dendritic cell antigen-2/CD303 + blasts, together with the absence of lineage specific antigens on tumour cells. In this report we present a case of BPDCN presenting with extramedullary and bone marrow involvement, extensively studied by flow cytometry and immunohistochemistry, who achieved complete remission after acute lymphoblastic leukemia like chemotherapy and allogeneic hematopoietic stem cell transplantation.